Optic Nerve Sonography in the Diagnostic Evaluation of Pseudopapilledema and Raised Intracranial Pressure: A Cross-Sectional Study - Masoud Mehrpour; Fatemeh Oliaee Torshizi; Shooka Esmaeeli; Salameh Taghipour; Sahar Abdollahi (Neurology Research International)
Introduction. Differentiating pseudopapilledema from papilledema which is optic disk edema and a result of increased ICP (intracranial pressure) is important and can be done with noninvasive methods like orbital ultrasound examination. Method. This was a cross-sectional study in which patients with optic nerve head swelling were referred for LP exam after optic nerve head swelling diagnosis confirmation and having normal brain imaging (CT scan). Before LP (lumbar puncture) exam the patients were referred for optic nerve ultrasound test of both eyes. Results. Considering 5.7 mm as the upper limit for normal ONSD (optic nerve sheath diameter), sensitivity and negative predictive value of optic sonography in diagnosis of pseudopapilledema are 100% for both eyes. Calculated accuracy validity of ONSD measurement in detecting pseudopapilledema is 90% for the right eye and 87% for the left eye. Conclusion. Our study demonstrated a close correlation between optic nerve sheath dilation on ocular ultrasound and evidence of elevated ICP with optic disk swelling. With the aid of noninvasive diagnostic tests we can avoid unnecessary concerns along with expensive and invasive neurological investigations while targeting the correct diagnosis in bilateral optic disk swelling. Our study showed optic nerve sonography as a reliable diagnostic method for further usage.